Seligman's Principles of Economics: A Reply and a Rejoinder - Taussig, F. W. (Quarterly Journal of Economics, 1906)
Journal Article Seligman's Principles of Economics: A Reply and a Rejoinder Get access Edwin R. A. Seligman, Edwin R. A. Seligman Columbia University Search for other works by this author on: Oxford Academic Google Scholar F. W. Taussig F. W. Taussig Harvard University Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 21, Issue 1, November 1906, Pages 151–165, https://doi.org/10.2307/1883753 Published: 01 November 1906